Exploring the cutting process of coaxial phase change fibers under optical characterization tests - Hammes, Nathalia (2024)
Urban heat islands (UHI) are a growing issue due to urbanization, causing citizens to suffer from the inadequate thermal properties of building materials. Therefore, the need for climateresistant infrastructure is crucial for quality of life. Phase change materials (PCMs) offer a solution by being incorporated into construction materials for thermoregulation. PCMs store and release heat as latent heat, adjusting temperatures through phase changes. Polymeric phase change fibers (PCFs) are an innovative technology for encapsulating PCMs and preventing leaks. This study produced PCFs via wet-spinning, using commercial cellulose acetate (CA, Mn 50,000) as the sheath and polyethylene glycol (PEG 2000) as the core. The PCFs were cut using a hot-cutting method at three different temperatures and washed with distilled water. Morphological analysis was conducted with a bright-field microscope, and chemical analysis was performed using Fourier transform infrared spectroscopy (FTIR) before and after controlled washing. Additionally, the washing baths were analyzed by UV-visible spectroscopy to detect PEG. The PCFs displayed a well-defined core-shell structure. Although some PEG 2000 leakage occurred in unsuccessful cuts, cuts at 50 °C showed sealed ends and less material in the baths, making it viable for civil engineering materials.